PENGARUH KESEHATAN LINGKUNGAN SEKOLAH TERHADAP SIKAP RELIGIUS SISWA DI MAN 4 DENANYAR JOMBANG TAHUN AJARAN 2024/2025 - Abdul Karim Assyafiie; Jumari Jumari (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The environmental health of schools has a significant correlation with the development of students' religious attitudes. A school environment that supports physical and psychosocial health tends to create an atmosphere conducive to the development of spiritual and religious values. Clean, safe, and comfortable school facilities can provide a sense of tranquility for students, allowing them to focus more on self-reflection and the search for meaning in life. Moreover, an environment that provides space for open and inclusive religious discussions and practices can also strengthen students' spiritual identity and commitment. This research aims to determine: (1) The Environmental Health of MAN 4 Denanyar Jombang; (2) Students' Religious Attitudes at MAN 4 Denanyar Jombang; (3) The Influence of School Environmental Health on Students' Religious Attitudes at MAN 4 Denanyar Jombang. This study uses a quantitative approach with an ex-post facto research design. It is considered a population study as the subjects are less than 100, specifically 50 students. Data collection techniques include observation, questionnaires, and documentation. The validity of the instruments is tested using Pearson Product Moment correlation, while reliability is tested using Cronbach’s Alpha formula. Pre-requisite analysis includes normality testing and correlation testing. Hypothesis testing involves simple linear regression equations.Based on the research findings: (1) The environmental health of the school yielded scores ranging from 50-56, with 3 respondents comprising 6% of the total, followed by scores in the moderate range of 57-63, involving 8 respondents at 16%. Next, scores from 64-70 were reported by 12 respondents, accounting for 24%. Scores ranging from 71-77 included 13 respondents, representing 26%, while the highest scores ranged from 78-85, with 14 respondents comprising 28%. (2) The religiosity of students showed scores ranging from 57- 60, with 7 respondents making up 14%, followed by scores in the moderate range of 61-64, involving 10 respondents at 20%. Next, scores from 65-68 were reported by 20 respondents, accounting for 40%. The highest scores, ranging from 69-72, included 13 respondents, representing 26%. (3) The influence of school environmental health on student religiosity amounted to 60.2%, with the remaining 39.8% attributable to other factors affecting student religiosity at MAN 4 Denanyar Jombang